Medical education: online activity using Project-based Methodology and Digital Technology (Research, Society and Development, 2022)
The Curriculum Guidelines for the Medicine Course recommends that medical training must be guided by the health needs of individuals and populations and must use methodologies that privilege the active participation of the student in the construction of knowledge and the integration of teaching, research, extension contents and assistance. The study aimed to develop a teaching-learning activity in a subject on Adult and Elderly Health IV (SAI IV), based on active methodology, educational technology and production of an educational resource in health education, in the online modality. Development research was carried out, in three stages: Analysis and exploration of the problem; Design and construction and Evaluation and reflection. A teaching-learning design was created (Virtual Practical Activity) that is developed in a Virtual Learning Environment, with six guiding modules: Content, Active Methodology, Interaction, Self-study, Evaluation and Collaboration/Reflection. The activity was innovative and stimulated students in the active development of new knowledge, as well as in the ability to value the knowledge that students bring from their experiences. As a result, the students produced educational resources, which were disseminated in the media, in addition to provoking the development of subsequent projects, such as developing a multiplayer online game for teaching gastrointestinal pathologies in the medical course.